2022
DOI: 10.3390/biomedicines10051069
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Time in Pregnancy: An Exploratory Study on Oxidative Stress Markers in the Placenta of Women with Obesity

Abstract: Regular moderate-to-vigorous physical activity (MVPA) and reduced sedentary time (ST) improve maternal glucose metabolism in pregnancy. More MVPA and less ST outside pregnancy increase antioxidant capacity, hence, are beneficial in preventing oxidative stress. The placenta is the first line of defense for the fetus from an adverse maternal environment, including oxidative stress. However, effects of MVPA and ST on oxidative stress markers in the placenta are unknown. The purpose of this study was to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Physical activity is important to mitigate this negative effect of obesity. We recently reported that increasing MVPA and reducing ST attenuate the oxidative stress state in the placentas of obese pregnant women [ 19 ]. In the present study, we observed that MVPA is associated with higher antioxidant capacity in cord blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity is important to mitigate this negative effect of obesity. We recently reported that increasing MVPA and reducing ST attenuate the oxidative stress state in the placentas of obese pregnant women [ 19 ]. In the present study, we observed that MVPA is associated with higher antioxidant capacity in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 19 ], physical activity was measured objectively by accelerometers (ActiGraph GT1M, GT3X+ or Actitrainer; Pensacola, FL, USA) at <20 weeks, 24–28 weeks, and 35–37 weeks. A minimum of three valid full day measurements per time-period, with a daily wear time of more than 480 min, were needed to be included in the analysis.…”
Section: Methodsmentioning
confidence: 99%